Interfaith Figures Communication Model in Building Religious Harmony in North Labuhanbatu Regency - Syukur Kholil; Yusnadi Yusnadi; Ibrahim Sihombing (Budapest International Research and Critics University, 2020)
This study about Interfaith Figures Communication Model in Building Religious Harmony in North Labuhanbatu Regency deals with the awareness of interfaith leaders in Labura of the importance of living harmoniously between religious communities, it is important for them to disseminate their understanding of how to build harmony and harmony between religious communities at the root of the clump (community). Therefore, religious figures